Pengaruh Media Video Pembelajaran Integral Dasar Terhadap Hasil Belajar Siswa Kelas XI MIPA SMA Negeri 1 Polokarto Kabupaten Sukoharjo Tahun Ajaran 2022/2023 - Widiyanto, Aan; Hadiprasetyo, Krisdianto; Exacta, Annisa Prima (Absis: Mathematics Education Journal, 2023)
The purpose of the study was to find out whether there is an influence of basic integral learning video media on learning outcomes for Class XI MIPA students at SMA Negeri 1 Polokarto, Sukoharjo Regency, in the 2022/2023 academic year. This study uses a type of experimental research with a quantitative approach. With a population of all class XI MIPA students at SMA N 1 Polokarto for the 2022/2023 academic year, Sukoharjo Regency, there are 142 students and 4 classes. In this study using purposive sampling technique. This consideration was taken based on the number of students between the two classes being the same and the standard deviation values being relatively the same. The two classes that became the experimental and control classes were XI MIPA 1 and XI MIPA 2 with basic integral discussion material. Learning outcomes can be seen in the hypothesis test, it is known that the value of the independent sample t-test, with H0 is accepted if tcount ? ttable and H0 is rejected if tcount < ttable by determining dk = n1 + n2 - 2 with a significant level of ? = 5%. It can be seen that tcount = -5.151 and ttable = 1.994. Then the calculation results can be seen that tcount < ttable, namely -5.151 <1.994 means that H0 is rejected., and the results of observations of student activity during activities on basic integral material the average value of the percentage of observations in the experimental and control classes , showing the results of student activity in the experimental class was higher than the control class. This can be seen from the percentage of the average value of the two observers who were carried out in the experimental class by 95% while in the control class by 83.3%. Based on the results of research data analysis, seen from the results of learning to test the hypothesis and the percentage of the average value of observations, it can be concluded that there is an influence of learning video media in helping to understand Basic Integral material on student learning outcomes in class XI MIPA SMA Negeri 1 Polokarto, Sukoharjo Regency, Academic Year 2022/2023 .